PENERAPAN PENDEKATAN REALISTIC MATHEMATICS EDUCATION UNTUK MENINGKATKAN HASIL BELAJAR SISWA PADA MATERISOAL CERITA TENTANG HIMPUNAN DI KELAS VII MTsN PALU BARAT - Lestari A., Ardhini (Jurnal Elektronik Pendidikan Matematika Tadulako, 2014)
This research aim to obtain a description about applying Realistic Mathematic Education (RME) approachto increase learning outcomes on the set word problemsmatter inclassVIIFMTsNPalu Barat. This was a classroom action researchÂ  which refers to the design of the research Kemmis and Mc. Taggart, that is planning, action and observation, and reflection.This research is executed in two cycles.The research results showed that applying of RME approach to increase learning outcomes onthe set word problemsmatterfollowing these steps, namel: (1)understanding thecontextualproblem, (2) solving problem, (3) comparinganddiscussing the answer, (4)concluding.In stepunderstandingof contextualissues, the teacherpresents thecontextualissuesandasks the studentstounderstand thegiven problem. In stepsolve the problem, along withhis groupof studentswere asked tosolve the problem. Ina stepto compare and discussanswers, severalgroupspresented the results ofthe workinggroupandother groupsto compareand commentifthere are differences inthe answerswith the group.In theconcludingstep, the teacher directsstudents tomake inferencesfromapayangbeen studied.